MOTHERS’ OVERPROTECTION AND EATING PROBLEMS IN COLLEGE STUDENTS: A MEDIATING ROLE OF EMOTION DYSREGULATION - Farah Iqbal,; Naqvi, Ghuncha; Sadia Saleem,; Sayyeda Taskeen Zahra, (Journal of Postgraduate Medical Institute, 2023)
Objectives: To find out the disordered eating behavior and its relationship with mother overprotectiveness and emotion dysregulation and to find out the mediating role of emotional dyregulation between mother’s overprotection and eating problems. Methodology: Correlational research design was used in this research. Through multistage sampling, data was collected from 300 college students (Men=166, Women=134). Three measures were used in this study which were EMBU-A, Eating Disorder Examination Questionnaire and Emotion Regulation Scale. Pearson product moment correlation was conducted to determine relationship among disordered eating behavior, mother’s overprotectiveness and emotional dysregulation. Mediation analysis was carried out by Hayes model bootstrapping approach. Results: Correlation analysis revealed that mother’s overprotection and emotion dysregulation were significantly positively correlated with eating problems (r = .13, p < .05) and eating problems (r = .24, p < .001). Moreover, emotion dysregulation significantly mediated the relationship of mother overprotection and eating problems = .21, SE = .05,. Conclusion: Emotions can shift the focus of eating behaviors while considering the role of gender and maternal bonding during the adolescence period. A healthier relationship demands positive maternal practices that helps in decreasing the prevalence of disturbed eating behaviors. Based on the results awareness needs to be created among mental health professional to arrange seminars and trainings for students and parents from both gender regarding the consequences of disordered eating behavior in their children.